2015
DOI: 10.1371/journal.pone.0127370
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Randomized, Controlled Trial of Osteopathic Manipulative Treatment on Preterms

Abstract: BackgroundDespite some preliminary evidence, it is still largely unknown whether osteopathic manipulative treatment improves preterm clinical outcomes.Materials and MethodsThe present multi-center randomized single blind parallel group clinical trial enrolled newborns who met the criteria for gestational age between 29 and 37 weeks, without any congenital complication from 3 different public neonatal intensive care units. Preterm infants were randomly assigned to usual prenatal care (control group) or osteopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
76
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(83 citation statements)
references
References 27 publications
4
76
0
3
Order By: Relevance
“…Four studies were conducted in Italy [2730] and 1 in Austria. [31] The publication period ranged from 2007 to 2015.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies were conducted in Italy [2730] and 1 in Austria. [31] The publication period ranged from 2007 to 2015.…”
Section: Resultsmentioning
confidence: 99%
“…All studies considered LOS as clinical outcome, 4 trials as primary outcome, [2730] whereas 1 considered it as a secondary outcome. [31] Further studies’ aims were: average daily gut symptoms, [27] costs, [2830] daily weight gain, [2830] meconium evacuation, full enteral feeding, and weight gain at discharge home.…”
Section: Resultsmentioning
confidence: 99%
“…Length of hospitalization, which varies inversely with GA and birth weight, 4 is a common measure of treatment success in the neonatal intensive care unit (NICU). 5 Osteopathy is a system of healing that employs manual techniques to diagnosis and treat "somatic dysfunction", which may manifest as restricted range of motion, tenderness, asymmetry and aberrant tissue texture. 5 Two previous trials have indicated a favorable effect of osteopathic manipulative therapy (OMT) on length of stay (LOS) for preterm infants.…”
mentioning
confidence: 99%
“…5 Osteopathy is a system of healing that employs manual techniques to diagnosis and treat "somatic dysfunction", which may manifest as restricted range of motion, tenderness, asymmetry and aberrant tissue texture. 5 Two previous trials have indicated a favorable effect of osteopathic manipulative therapy (OMT) on length of stay (LOS) for preterm infants. 6,7 In this Italian trial, researchers randomized 720 preterm infants (GA 29-37 weeks) into two groups: OMT plus usual care and usual care alone.…”
mentioning
confidence: 99%
See 1 more Smart Citation